Influence of calcium carbonate and slip agent addition on linear medium density polyethylene processed by rotational molding - Baumer M.I. (2014)
In this paper, the influence of calcium carbonate and slip agent on linear medium density polyethylene (LMDPE) processed by rotational molding was evaluated. LMDPE was dry blended with different CaCO3 masterbatch ratios, erucamide slip agent and then extruded, micronized and rotomolded. The powder samples were characterized using MFI (Melting flow index), dry flow and bulk density. The characterization of rotomolded samples properties was performed by DSC (Differential scanning calorimetry), microscopy analysis, izod impact and tensile test. The results pointed out that the CaCO3 addition modifies the bulk density compared to neat LMDPE, but did not significantly affect the dry flow and MFI. The erucamide addition decreased the dry flow and increased the bulk densities. The porosity degree data showed that CaCO3 addition in the LMDPE increased the quantity of pores. The DSC results showed no significant difference in the crystallinity degree. The behavior of porosity led to a decrease in the mechanical properties of LMDPE with the CaCO3 addition.